Odpowiedzi

2010-03-09T18:05:42+01:00
A) 5t+3=t+19
4t=16
t=4
b)4(x+1)=6x
4x+4=6x
-2x=-4
2x=4
x=2
c)1/2(k+1)=k-2,6
1/2k+1/2=k-2,6
-0,5k=-2,6-0,5
0,5k=3,1
k=6,2
d)4x-3=3x+5
4x-3x=5+3
x=8
e)5-2(y+3)=8
5-2y-6=8
-2y=8+6-5
-2y=9
y=-4,5
2010-03-09T18:08:21+01:00
A) 5t+3=t+19
4t=16/4
t=4

b)4(x+1)=6x
4x+4=6x
2x=4/2
x=2

c)1/2(k+1)=k-2,6
1/2k+1/2=k-2,6
1/2k=3,1/ 1/2
k=6,2
d)4x-3=3x+5
x=8
e)5-2(y+3)=8
5-2y-6=8
-2y=9/-2
y=4,5
2010-03-09T18:10:12+01:00
A)5t-t=19-3
4t=16/:4
t=4
b)4x+4=6x
4x-6x=-4
-2x=-4/:(-2)
x=2
c)0,5k+0,5=k-2,6
0,5k-k=-2,6-0,5
-0,5k=-3,1/:(-0,5)
k=1,55
d)4x-3x=3+5
x=8
e)5-2y-6=8
-2y=8-5+6
-2y=9/:(-2)
y=-4,5